2004
DOI: 10.1137/s1064827503421707
|View full text |Cite
|
Sign up to set email alerts
|

New Geometric Immersed Interface Multigrid Solvers

Abstract: elliptic interface problems using the maximum principle preserving schemes. In this paper, we improve on this method by giving a new interpolator for grid points near the immersed interface and a new restrictor that guarantees the coarse-grid matrices are M-matrices. We compare this new restrictor to injection and the transpose of interpolation. We show that the number of V-cycles is constant as the mesh size decreases and increases only slightly as the ratio of the discontinuous problem coefficient grows at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(72 citation statements)
references
References 8 publications
0
72
0
Order By: Relevance
“…In [1][2][3], multigrid methods were designed specifically for interface problems discretized by immersed interface methods [13,15]. For interfaces with moderate curvature, the method proposed in [1] produced satisfactory performance. AMG is employed in [7] to solve the resulting linear system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [1][2][3], multigrid methods were designed specifically for interface problems discretized by immersed interface methods [13,15]. For interfaces with moderate curvature, the method proposed in [1] produced satisfactory performance. AMG is employed in [7] to solve the resulting linear system.…”
Section: Introductionmentioning
confidence: 99%
“…AMG is employed in [7] to solve the resulting linear system. It is observed that convergence becomes worse when the problem has high-contrast coefficients and thus many more iterations are needed to achieve reasonable accuracy [1].…”
Section: Introductionmentioning
confidence: 99%
“…For example, if we rewrite the boundary integral equation (19) as (24) with (25) and rewrite the boundary integral equation (21) as (26) with (27) the application of the GMRES iterative method to solving (24) and (26) simply requires computation of ḡ D , ḡ N and the actions φ, *ψ of the operators , * on φ and ψ, respectively. Once again, the right hand sides of (25) and (27) can be approximated by limit values of approximate solutions to the Dirichlet BVP while direct evaluation of volume and boundary integrals are avoided.…”
Section: Boundary Integral Equationsmentioning
confidence: 99%
“…Suppose that an approximation to the double layer potential density φ(p) is known as an intermediate result of the simple iteration (22) or the GMRES iteration for the boundary integral equation (19) or (24). Denote the approximate density by φ υ ≡ φ ν (p).…”
Section: Computation Of the Volume And Boundary Integralsmentioning
confidence: 99%
See 1 more Smart Citation